Practicing Religious Moderation among Muslims, Buddhists, and Hindus in North Lombok - Jayadi, Suparman; Ridho, Abdul Rasyid (FIKRAH, 2024)
Diversity in recent times has its challenges, especially maintaining social harmony in the midst of potential religious conflicts. The practice of religious moderation is very important in fostering tolerance and peace between religions. This article aims to explore and implement the practice of religious moderation among the Muslim, Buddhist and Hindu communities in Juara Timur Village, North Lombok, Indonesia, with a focus on Pujawali rituals as a case  study. This article uses qualitative methods to present field data, by conducting observations, then in-depth interviews with informants related to values and norms in religious moderation practices, and conducting documentation. The findings of this study show that community adherence to local traditions and mutual respect for different religious practices can make a significant contribution to maintaining social cohesion. The practice of Pujawali Ritual is an example of how interfaith interaction based on local wisdom and cultural practices can increase social solidarity and religious comfort and security to date. This study contributes to the importance of values and norms in the practice of religious moderation to realize peace and prevent social conflicts and can be used as a role model in various regions in Indonesia.